Degradation of α-nitroso-β-naphthol by UVA-B activated peroxide, persulfate and monopersulfate oxidants in water. (20th November 2019) - Lu, Chao; Yao, Jun; Knudsen, Tatjana Šolević; Amde, Meseret; Gu, Jihai; Liu, Jianli; Li, Hao; Zhang, Junyang
Abstract: Flotation reagents, especially new chelating agents represented by α-nitroso-β-naphthol, are the main components of cobalt mining drainage. This study reports the degradation of α-nitroso-β-naphthol by simulated UVA-B (280–400 nm) activated systems using three common oxidants, hydrogen peroxide, sodium persulfate and potassium monopersulfate at a laboratory scale using a photoreactor. Parameters which can affect the degradation process were investigated and comparison of the degradation performance of the three systems were made. Based on the results, UVA-B/sodium persulfate system exhibited best performance towards the removal of α-nitroso-β-naphthol with a lower cost of oxidant and energy consumption compared to the others. The removal efficiency was found to increase as the oxidant dosage and the UVA-B power increases. Only potassium monopersulfate could be activated by bicarbonate and chloride ions, and SO4 2− has insignificant effect on the removal efficiency of α-nitroso-β-naphthol for all systems while NO3 − inhibited the degradation of α-nitroso-β-naphthol. In the UVA-B/hydrogen peroxide system, the hydroxyl radical had a leading role in the degradation of α-nitroso-β-naphthol, while in the other two systems, the degradation of α-nitroso-β-naphthol was mainly caused by the hydroxyl and sulphate radicals. Ten major intermediates from α-nitroso-β-naphthol degradation in the three oxidation systems were identified by gas chromatography and mass spectrometry. In summary, this report could be a great input in developing UVA-B activated oxidants-based treatment technologies. The UVA-B/sodium persulfate system is strongly recommended for its consideration in the treatment of mine impacted wastewaters. Graphical abstract: Image 1 Highlights: Degradation of α-nitroso-β-naphthol was made in UVA-B/HP, UVA-B/SPS and UVA-B/PMS systems. UVA-B/SPS was found to be the most efficient, economical and energy-saving. High concentration of Cl − enhances the degradation of αNβN in UVA-B/PMS systems. 10 by-products from the degradation of αNβN in three UVA-B/oxidant systems were detected. Abstract : UVA-B/SPS is the most efficient, economical and energy-saving technique for the degradation of αNβN compared to UVA-B/HP and UVA-B/PMS systems.